The Effect of Green Marketing and Brand Image of Somethinc Cosmetic Products on Students’ Loyalty at FEBI UINSU - Ritonga, Mei Anriani; Syarvina, Wahyu; Atika, Atika (Moneter: Jurnal Keuangan dan Perbankan, 2025)
The Somethinc brand in 2024 is experiencing tight competition with other local brands that are also growing rapidly. This condition is a challenge for the owner of the Somethinc company to maintain its position as the main choice in the minds of consumers. Moreover, many other companies are increasingly showing concern for environmental issues, so they have adopted the concept of green marketing which may be more attractive and effective than the approach used by Somethinc. Within the scope of this research project, the objective is to ascertain the impact that green marketing and the brand image of certain cosmetic goods have on the loyalty of student consumers. An strategy that is quantitative and makes use of a questionnaire distribution method is used in this investigation. This research is being conducted with the participation of students who are enrolled in the Faculty of Islamic Economics and Business at the State Islamic University of North Sumatra. A method known as purposive sampling is used in this investigation. The strategy that is used is known as Structural Equation Modeling (SEM), which is based on variance and utilizes the Partial Least Square (PLS) method. The results of the study is suggest that the Green Marketing strategy and brand image used by Somethinc cosmetic goods are factors that lead to an increase in the level of student loyalty.